CSC430: Computer Programming and Applications / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2022)
This course is designed for students to study engineering programming. Fundamental concepts and principles of the chosen computer programming language are covered in this course. Considerable emphasis is placed on the understanding and application of computer programming.